1971
DOI: 10.1002/1097-0142(197106)27:6<1455::aid-cncr2820270628>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic study of papillary serous tumors of the ovary

Abstract: Electron microscopic evaluation was performed in a series of papillary serous tumors of the ovary, including 4 cystadenomas, 2 cystadenocarcinomas, and 2 tumors with questionable histologic evidence of malignancy. Marked nuclear irregularity was found in the cells of those tumors which were malignant by histologic criteria. Nuclei of cells from benign tumors had a regular shape and outline, with only shallow indentations. In the cases with borderline malignant changes, an intermediate degree of nuclear irregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Multiciliated cells, such as those shown in Figure 10a and b, have previously been reported in serous carcinomas and are more often found in low-grade serous carcinomas and serous tumors of borderline malignancy originating in the ovary and peritoneum. 23,24,[69][70][71][72] Neither in the present study nor in previous investigations have these cells been found in mesotheliomas. Cells presenting a solitary cilium or a few cilia have frequently been found in serous carcinomas, including those of high-grade malignancy; however, their occurrence in mesotheliomas is exceedingly rare.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Multiciliated cells, such as those shown in Figure 10a and b, have previously been reported in serous carcinomas and are more often found in low-grade serous carcinomas and serous tumors of borderline malignancy originating in the ovary and peritoneum. 23,24,[69][70][71][72] Neither in the present study nor in previous investigations have these cells been found in mesotheliomas. Cells presenting a solitary cilium or a few cilia have frequently been found in serous carcinomas, including those of high-grade malignancy; however, their occurrence in mesotheliomas is exceedingly rare.…”
Section: Discussioncontrasting
confidence: 89%
“…Similar to previous ultrastructural studies, large collections of intermediate filaments arranged in tonofibrillar bundles and intracytoplasmic lumens covered by microvilli were common findings in mesotheliomas, [65][66][67] but not in serous carcinomas. [68][69][70] No intracytoplasmic lumens were identified in any of the serous carcinomas investigated, and only rare small bundles of intermediate filaments were found in a few cases. Another finding that was helpful in distinguishing serous carcinomas from mesotheliomas was the presence of multiciliated cells in serous carcinomas, but not in mesotheliomas.…”
Section: Discussionmentioning
confidence: 87%